Dietary Supplementation of Strawberry Improves Vascular Inflammation Without Altering Metabolic Milieu in High-fat Diet Fed C57BL/6 J Mice (P06-086-19) - Miller, James (Curr Dev Nutr, 2019)
OBJECTIVES: Metabolic syndrome (MetS) is an important risk factor for cardiovascular mortality and vascular inflammation plays a major role in the development of vascular complications. We tested the hypothesis that dietary strawberries (SB) attenuate vascular inflammation in MetS and this is due to a direct effect of SB on the vasculature. METHODS: Seven-week-old male C57BL/6 J mice consumed rodent diets with 10% kcal from fat (control diet fed mice; CD) or 60% kcal from fat (high-fat diet fed mice; HFD) for 12 weeks and subgroups of CD and HFD mice were fed a 2.35% freeze-dried SB supplemented diet (CD + SB or HFD + SB). This dose in mice is equivalent to two servings of SB (∼160 g) per day in humans. HFD model shares many vascular phenotypes with human MetS including vascular inflammation. The following analyses were completed after 12-week treatment: body weight; food intake; body composition; respiratory exchange ratio (RER), energy expenditure and activity (in light and dark cycle by Comprehensive Laboratory Animal Monitoring System); fasting and non-fasting blood glucose; glucose and insulin tolerance tests; and vascular inflammation (binding of fluorescent labelled mouse monocytes WEHI78/24 to aortic vessel). RESULTS: HFD mice exhibited increased body weight, reduced lean body mass, increased body fat, reduced RER (in both light and dark cycle), increased fasting and non-fasting blood glucose, and impaired glucose and insulin tolerance compared to CD mice (P < 0.05). SB supplementation does not alter body weight, body fat, lean body mass, blood glucose, glucose or insulin tolerance in CD + SB and HFD + SB mice. The energy expenditure and activity were similar among the groups. The aortic vessel from HFD exhibited an increased binding to WEHI 78/24 monocytic cells vs CD mice. However, SB supplementation reduced monocyte binding to the vessel in HFD + SB vs HFD mice (P < 0.05). CONCLUSIONS: Strawberry supplementation improves vascular inflammation in HFD mice without altering metabolic milieu. This study indicates that the beneficial vascular effects of SB may not be due to a secondary effect but could be a direct effect on the vasculature. Strawberry consumption may be a potential adjunct strategy to prevent vascular complications in MetS. FUNDING SOURCES: USDA grant (to ABPV), University of Utah Undergraduate Research Opportunity Program Award (to MNP, JEM, ASO, SS).